The Townsite of Semibratneye (Labrys) Results of Excavations in 2006–2009 - Goroncharovskiy, Vladimir (Hyperboreus, 2015)
A survey of the excavations at the townsite of Semibratneye/Labrys (28 km to the Nord-East of Gorgippia) conducted by the Bosporan expedition of the Institute for the History of Material Culture, RAS, in 2006–2009.